Surface Physicochemical Properties of Globulin-P Amaranth Protein - Aphalo, Paula (2004)
Globulin-P, the polymerized 11S amaranth globulin, is composed of 280 kDa unitary molecules (UM, 23%) and aggregates larger than 500 kDa (A, 70%). Antibodies against these proteins were prepared to study their surface characteristics and to assess their homology with other storage proteins. Results showed that globulin-P unitary molecules and aggregates had similar reactive surfaces. A polypeptide of 56 kDa was found to be the most reactive to the antibodies assayed, followed by the acidic polypeptides. Such results support previous information, according to which these polypeptides appeared to be the most exposed on the molecule surface. Globulin-P fraction presented cross-reactivity with the remaining amaranth protein fractions: 11S-globulin, glutelins, and albumins. Globulin-P and 11S-globulin showed similar reactive surfaces whereas glutelin and albumins presented a lower cross-reactivity. The reactivity of the glutelin fraction depended on its sequence. Globulin-P fraction presented cross-reactivity with quinoa globulins, and to a lesser extent with globulins of sunflower and rice. Moreover, the anti-Gp serum was unable to detect either conformational or sequence epitopes in globulins of soybean, wheat, buckwheat, rice, and rye.